2019
DOI: 10.1038/s41598-019-42049-5
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of combinatorial treatments composed of transition-metal/antibiotics against Mycobacterium tuberculosis

Abstract: Notwithstanding evidence that tuberculosis (TB) is declining, one of the greatest concerns to public health is the emergence and spread of multi-drug resistant strains of Mycobacterium tuberculosis (MDR-TB). MDR-TB are defined as strains which are resistant to at least isoniazid (INH) and rifampicin, the two most potent TB drugs, and their increasing incidence is a serious concern. Recently, notable efforts have been spent on research to pursue novel treatments against MDR-TB, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Despite taking a backstage role after the advent of antibiotics, silver has been continuously used in different forms [1,2]. Furthermore, due to the multidrug resistance crisis, the utilization of silver as a component of combination therapies or other novel formulations has regained interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite taking a backstage role after the advent of antibiotics, silver has been continuously used in different forms [1,2]. Furthermore, due to the multidrug resistance crisis, the utilization of silver as a component of combination therapies or other novel formulations has regained interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial treatments composed of isoniazid/silver exhibited a synergistic bactericidal effect in an isoniazid-resistant clinical strain of M. tuberculosis (Montelongo-Peralta et al, 2019). Moreover, a previous study showed the ability of silver to potentiate the activity of a broad range of antibiotics against Gram-negative bacteria, as well as to restore antibiotic susceptibility (re-sensitizing) to a resistant bacterial strain (Morones-Ramirez et al, 2013).…”
Section: Metal Nanoparticle-based Combinatorial Treatmentsmentioning
confidence: 89%
“…Combinatorial treatments composed of isoniazid/silver exhibited a synergistic bactericidal effect in an isoniazid-resistant clinical strain of M . tuberculosis ( Montelongo-Peralta et al, 2019 ).…”
Section: The New Therapeutic Alternatives: Input From Recent Studiesmentioning
confidence: 99%
“…One of the most widely used combinatorial formulations in clinical practice is amoxicillin with clavulanic acid, where amoxicillin is an inhibitor of peptidoglycan synthesis while clavulanic acid inhibits the β-lactamase enzyme which degrades amoxicillin ( Huttner et al., 2019 ). Similar approaches combine two molecules which each independently exhibit antimicrobial activity and combine the dosing for treatment ( Montelongo-Peralta et al., 2019 ; Opalski et al., 2020 ). Many of these combinations are designed such that the two antimicrobials act via different mechanisms, ideally each enhancing the activity of the other.…”
Section: Introductionmentioning
confidence: 99%